24 Mediastinal Ectopic Parathyroid Adenoma Causing Malignant Hypercalcaemia in a Young Female - a Case Report and Review of Literature. (28th February 2022) - Bell, A.; Razzaq, Z.; Mustafa, H.; Redmond, H.P.
Abstract: Ectopic parathyroid tissue can pose difficulties in diagnosis and management of patients with hyperparathyroidism. Due to the embryological origins of the inferior parathyroid glands from the 3 rd pharyngeal arch where they develop with the thymus; they can have variable anatomical locations, including the anterior mediastinum. While the incidence of ectopic parathyroid glands varies in the literature mediastinal parathyroid tissue is extremely rare. This anatomical variation has important diagnostic and surgical ramifications for patients and is an important topic for trainees in medical endocrinology, endocrine surgery, and cardiothoracic surgery to be aware of. We present the case of a 22-year-old woman who presented as an emergency with severe hypercalcaemia. Who was subsequently found to have an ectopic mediastinal parathyroid adenoma. She underwent surgery within days of her initial presentation providing her with an immediate cure and restoring her calcium homeostasis. Despite diagnostic and operative challenges, combined care from our endocrine and cardio-thoracic surgical teams ensured an uneventful post-operative recovery for this patient.